If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3y = -28 Solving 4x + -3y = -28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 4x + -3y + 3y = -28 + 3y Combine like terms: -3y + 3y = 0 4x + 0 = -28 + 3y 4x = -28 + 3y Divide each side by '4'. x = -7 + 0.75y Simplifying x = -7 + 0.75y
| 5/4-(1/8)x=11/3-(5/6)x | | y+5=15x+10 | | 2n+13n=75 | | 3(4x+5)+2x=22 | | -40=8n-8 | | 7500.00+155x=0 | | -7=v-6 | | -11/3-(5/6)x=-1/22+(5/6)x | | x^3-7x^2-17x-9= | | 3(4x-5)+8=-67 | | 3(x+2)=4+2(x-3) | | -4f+1=16 | | 16+3x=9x+22 | | 25x^3+10x^2+x= | | x*x*x+2x*x-5x= | | 3g+3(-5+5g)=1-g | | 3ln(X)+ln(24)=ln(3) | | -6(3)-20=-2(3)+4(1-3(3)) | | 3x+50=90 | | 2.7q-5.6-5.8q=-4.1q-2.1 | | 7x+3=5x-15 | | 3x-50=90 | | 3x-50=120 | | y=3x^2+9x-30 | | C+273.15=k | | 3x-8=2(x-4)+x | | 12-3x=o | | 16y=480 | | 20-93=8a+51 | | 5x-11=x-24 | | 5(2x-4)=10x-9 | | x*x-5x= |